Overexpression of MRP3 in HeLa-UGT1A9 Cells Enhances Glucuronidation Capability of the Cells - Zhou, Qiong; Xia, Bijun; Yin, Taijun; He, Yu; Ye, Ling; Hu, Ming (Current Drug Metabolism, 2021)
Background: The interplay between phase II enzymes and efflux transporters leads to extensive metabolism and low systemic bioavailability of flavonoids. Objective: In this study, the dynamic interplay between multiple UGTs and multiple efflux transporters that occur inside the cells was fully investigated. Methods: A new HeLa-UGT1A9-MRP3 cell was established to overexpress two dominant efflux transporters MRP3 and BCRP, and two UGT isoforms UGT1A9 and UGT1A3. The metabolism and glucuronides excretion for a model flavonoid genistein were determined in HeLa-UGT1A9-MRP3 cells and HeLa-UGT1A9-Con cells that overexpressed one UGT (1A9) and one efflux transporter (BCRP). Results: The excretion rate grew nearly 6-fold, cellular clearance of glucuronides increased about 3-fold, and fraction of genistein metabolized (fmet) increased (14%, p<0.01) in the new cells. Small interfering (siRNA)-mediated MRP3 functional knockdown resulted in marked decreases in the excretion rates (26%-78%), intracellular amounts (56%-93%), and cellular clearance (54%-96%) in both cells, but the magnitude of the differences in HeLa- UGT1A9-Con cells was relatively small. Reductions in fmet values were similarly moderate (11%-14%). In contrast, UGT1A9 knockdown with siRNA caused large decreases in the excretion rates (46%-88%), intracellular amounts (80%-97%), cellular clearance (80%-98%) as well as fmet value (33%-43%, p<0.01) in both UGT1A9 cells. Comparisons of the kinetic parameters and profiles of genistein glucuronidation as well as UGT mRNA expression suggest that HeLa-UGT1A9-MRP3 has increased expression of both MRP3 and UGT1A3. Conclusion: The newly engineered HeLa-UGT1A9-MRP3 cells is an appropriate model to study the kinetic interplay between multiple UGTs and efflux transporters, and a promising biosynthetic tool to obtain flavonoid glucuronides of high purity.
Keywords: flavonoid